Pengaruh Pertumbuhan Modal Dan Pertumbuhan Penjualan Terhadap Laba Bersih Pada Perusahaan Food nd Beverage Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2013 - Herniyati Sitohang; Azli Fahrizal; Muhammad Luthfi (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2015)
Abstract. The increas in corporate profits shows in the large amount of capital and high sales. when the capitaland sales of high-owned company. the profits from the company will increase. This study aimed to examine theeffect of capital growth and income to net sales growth in Food And Beverage Company Listed In IndonesianStock Exchange. The population in this study was 20 Food And Beverage Company Listed On The IndonesianStock Exchange period 2010-2013. The sample in ths study were 13 companies will be observed 4 (four) so thatthe number of observation periods of 52 observations. The data used are the financial statemens Listed InIndonesian Stock Exchange (www.idx.co.id). The analytical method used in multiple linear regression. Basedon the results of this study concluded that jointly or individually partial orcapital growth and sales growth hadno significant effect on net income.